Burden of Disease and Cost of Chronic Hepatitis C Virus Infection in Canada - Robert P Myers; Mel Krajden; Marc Bilodeau; Kelly Kaita; Paul Marotta; Kevork Peltekian; Alnoor Ramji; Chris Estes; Homie Razavi; Morris Sherman (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Chronic infection with hepatitis C virus (HCV) is a major cause of cirrhosis, hepatocellular carcinoma and liver transplantation.